Evaluation and refinement of a handheld health information technology tool to support the timely update of bedside visual cues to prevent falls in hospitals. Issue 2 (June 2018) - Teh, Ruth C.-A.; Visvanathan, Renuka; Ranasinghe, Damith; Wilson, Anne
ABSTRACT: Aim: To evaluate clinicians' perspectives, before and after clinical implementation (i.e. trial) of a handheld health information technology (HIT) tool, incorporating an iPad device and automatically generated visual cues for bedside display, for falls risk assessment and prevention in hospital. Methods: This pilot study utilized mixed-methods research with focus group discussions and Likert-scale surveys to elicit clinicians' attitudes. The study was conducted across three phases within two medical wards of the Queen Elizabeth Hospital. Phase 1 (pretrial) involved focus group discussion (five staff) and surveys (48 staff) to elicit preliminary perspectives on tool use, benefits and barriers to use and recommendations for improvement. Phase 2 (tool trial) involved HIT tool implementation on two hospital wards over consecutive 12-week periods. Phase 3 (post-trial) involved focus group discussion (five staff) and surveys (29 staff) following tool implementation, with similar themes as in Phase 1. Qualitative data were evaluated using content analysis, and quantitative data using descriptive statistics and logistic regression analysis, with subgroup analyses on user status ( P ⩽ 0.05). Results: Four findings emerged on clinicians' experience, positive perceptions, negative perceptions and recommendations for improvement of the tool. Pretrial, clinicians were familiar with using visual cues in hospital falls prevention. They identified potential benefits of the HIT tool in obtaining timely, useful falls risk assessment to improve patient care. During the trial, the wards differed in methods of tool implementation, resulting in lower uptake by clinicians on the subacute ward. Post-trial, clinicians remained supportive for incorporating the tool into clinical practice; however, there were issues with usability and lack of time for tool use. Staff who had not used the tool had less appreciation for it improving their understanding of patients' falls risk factors (odds ratio 0.12), or effectively preventing hospital falls (odds ratio 0.12). Clinicians' recommendations resulted in subsequent technological refinement of the tool, and provision of an additional iPad device for more efficient use. Conclusion: This study adds to the limited pool of knowledge about clinicians' attitudes toward health technology use in falls avoidance. Clinicians were willing to use the HIT tool, and their concerns about its usability were addressed in ongoing tool improvement. Including end-users in the development and refinement processes, as well as having high staff uptake of new technologies, is important in improving their acceptance and usage, and in maximizing beneficial feedback to further inform tool development.